2016
DOI: 10.1186/s12859-016-1374-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modeling and lead design of substituted zanamivir derivatives as potent anti-influenza drugs

Abstract: BackgroundInfluenza virus spreads infection by two main surface glycoproteins, namely hemagglutinin (HA) and neuraminidase (NA). NA cleaves the sialic acid receptors eventually releasing newly formed virus particles which then invade new cells. Inhibition of NA could limit the replication of virus to one round which is insufficient to cause the disease.ResultsAn experimentally reported series of acylguanidine zanamivir derivatives was used to develop GQSAR model targeting NA in different strains of influenza v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…5,6 Nevertheless, it has a strong molecular polarity, which leads to low absorbability by oral administration, making its administering inconvenient for children. 7 Selenium (Se) is an essential trace element in human body. Adequate Se helps to maintain activity of NK cells and promote proliferation of T cells, which are signicant for antiviral immunity.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Nevertheless, it has a strong molecular polarity, which leads to low absorbability by oral administration, making its administering inconvenient for children. 7 Selenium (Se) is an essential trace element in human body. Adequate Se helps to maintain activity of NK cells and promote proliferation of T cells, which are signicant for antiviral immunity.…”
Section: Introductionmentioning
confidence: 99%
“…HIA is another essential factor of significant consideration during the drug design, optimization, and selection of orally active drug molecules. The intestine is the most important site of absorption for an orally consumable drug and an important parameter in the search for potential drug-likeness of a lead molecule [ 206 , 207 ].…”
Section: Ligand-based Drug Discovery Toolsmentioning
confidence: 99%
“…In all, 11 residues from all drugs have been identified that participate in hydrogen bond formation. These are: ARG118, GLU119, ASP151, ARG152, SER153, ARG156, TRP178, GLU227, GLU277, ARG371, GLU425 [10,42] and are shown in (Table 2 in Supplementary material). Out of these 11, those 6 common residues (GLU119, ARG152, GLU227, ARG371, ARG156, GLU277) have been selected that are present for the maximum time duration at different time intervals.…”
Section: Selection Of Common Residues For Hydrogen Bond Formationmentioning
confidence: 99%